The Effect of Peer Education Health Promotion on Adolescents Knowledge and Attitudes Regarding Reproductive Health Triad - Dian Mayasari; Dian Asih Ning Utami; Zidny Muti’aturohmah (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
Adolescents in Indonesia currently have problems that are usually called TRIAD KRR, namely Three Basic Risks of Adolescent Reproductive Health Threats related to sexuality, HIV/AIDS, and drugs with prevalence showing that the young generation of Indonesia has 23 cases where 9 have had sexual intercourse and 14 have used drugs in 2023. Adolescents with these reproductive health problems are caused by limited knowledge and attitudes about reproductive health. Peer education is a method that can improve adolescent knowledge and attitudes related to reproductive health. The purpose of this study was to analyze The Effect of Peer Education Health Promotion on Adolescents Knowledge and Attitudes Regarding Reproductive Health Triad The design is Pre Experimental Designs, with a Pre and Post One Group Design. Sampling used a purposive sampling technique. The population is all students with a sample size of 51 respondents. The research instrument is a questionnaire on knowledge and attitudes about TRIAD KRR that has been tested for validity and reliability. Data analysis used the Wilcoxon test to measure differences between two data groups. The results of the study revealed an effect of health education using the peer education method on the level of knowledge and attitudes after being given health education with a p value of <0.001 (<0.05).